(untitled) (Research, Society and Development, 2021)
Dentistry, like all science, is growing and improving its techniques. The immediate load is proof of this in the implantology area. Implants are inserted in a single session, and after a few hours the prosthesis is installed on the implants, allowing the patient to chew and return to social life. Among the basic requirements for its implementation is a judicious study of each case. Patients are subjected to careful evaluation of their systemic and occlusal health and of their bone volume and bone quality, which allows immediate fixation of the implant to the bone. Conventionally, the implant is fixed in the bone bed and is subjected to a second surgical intervention within 4 to 6 months to expose the prosthetic contact surface and place the prosthesis definitively. In the immediate load, the titanium fixation is attached to the bone and then the fixed prosthesis is installed in a single session. Our objective is to conduct a literature review on the current stage of implants with immediate load in the jaw and to describe an accompanying 1-year clinical case. With the current survey of the topic, we observe that the immediate load in the jaw is still a viable alternative to rehabilitation in edentulous patients.